2014
DOI: 10.5688/ajpe78363
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Science and Practice in Pharmacy Curricula

Abstract: An integrated curriculum is one where the summation of different academic disciplines forms a coherent whole and, importantly, where the relationships between the different disciplines have been carefully and strategically considered when forming the composite. Within pharmacy curriculum integration is important in order to produce graduates who have the capacity to apply their knowledge to a range of complex problems where available information is often incomplete. This paper discusses the development of an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 33 publications
3
69
0
Order By: Relevance
“…Previous researches demonstrated that integrated pharmacy curricula especially between didactic and experiential components can help students develop their own integrations. 3,[34][35][36][37] In the future, similar studies should focus on students exiting the program to better assess performance of the program rather than individual courses. Also, this will enable the elimination of some confounding factors associated with the study and better assess the need for integrated courses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous researches demonstrated that integrated pharmacy curricula especially between didactic and experiential components can help students develop their own integrations. 3,[34][35][36][37] In the future, similar studies should focus on students exiting the program to better assess performance of the program rather than individual courses. Also, this will enable the elimination of some confounding factors associated with the study and better assess the need for integrated courses.…”
Section: Discussionmentioning
confidence: 99%
“…2 Modern pharmacy curriculum is patient oriented, as it emphasizes on evidence-based medicine and integrates science and practice. 3,4 The College of Pharmacy (CP) in which this study was conducted has obtained was established in 2007 offering BSc pharmacy degree with patient-oriented curriculum. In addition to the national accrediting board in UAE, the college has also obtained the Accreditation Council for Pharmacy Education (ACPE) international certification and is offering a new MSc program in Clinical Pharmacy.…”
Section: Introductionmentioning
confidence: 99%
“…The PTD approach is task-oriented and task-based learning is the core strategy of the curriculum. Some other researchers have also agreed that task-based learning is a suitable strategy for adult learners since learning could be more motivated and more individualized for adult learners via task-based learning (Husband and Todd, 2014). 3) Learner analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The project was initially necessitated by new, external regulatory-accreditation requirements for curriculum integration across a five-year programme. Local practitioners wished to incorporate pedagogically-integrated models (e.g., Harden, 2000) and examine international comparators (e.g., Husband et al, 2014).…”
Section: An Example Of a Task Designmentioning
confidence: 99%